PENGARUH PROJECT BASED LEARNING TERHADAP KREATIVITAS PESERTA DIDIK MATA PELAJARAN PENDIDIKAN PANCASILA DI SMAN 21 SURABAYA - Astutik, Sri Puji; Listyaningsih (Universitas Negeri Surabaya (Unesa), 2024)
The study aims to test whether or not the project based learning model has an influence on the creativity of students in Pancasila Education subjects. The study is a quantitative study with a quasi-experimental approach the design of non-equivalent control groups using cluster random sampling technique with a total sample of 70 students. This research data collection technique uses observations, tests, student worksheets, and documentation. The data obtained was analyzed using the Kolmogorov Smirnov normality test, Levene's homogenity test and the paired sample t-test. The results of this study show that learning using project based learning model can enhance the creativity of students on the learning material from the wealth of tradition. This is demonstrated by the data of creativity using tests and LKPD higher experimental class than the control class is 83.92 > 69. The average value of the creativity indicator of originality the experiment class is 77.85%, the fluency indicator is excellent with a percentage of 94.28%, the flexibility includes a good category with a percent of 85% and the average values of the elaboration indicator are good with a rate of 77.14% and based on the test hypothesis paired sample t-test obtained a Sig. (2-tailed) score of 0.024 < 0.05, so H0 was rejected and Ha accepted, which means that there is a difference in creativity of learners before and after the training with the PjBL model so that it can be said that there was an influence of the project based learning model on student creativity in the teaching subjects of Pancasila Education at SMAN 21 Surabaya.